Criminal Penalties in Cyberspace: Between the Development of Digital Democracy and Authoritarianism - Emi Puasa Handayani; Zainal Arifin; Zico Junius Fernando (Universitas Negeri Semarang, 2025)
This study examines the implementation of Articles 27, 28, and 45 of the Information and Electronic Transactions Law (UU ITE) in the context of freedom of expression and digital democracy in Indonesia, both before and after the 2016 and 2024 amendments. Utilizing a normative approach that integrates conceptual, comparative, and futuristic methods, the research aims to analyze how these regulatory changes affect political participation in cyberspace and foster a climate of surveillance that may hinder digital democracy. This study also employs positivist legal theory, justice theory, and human rights principles to understand the socio-political and legal implications of these provisions. The findings reveal that Article 27 on defamation, Article 28 on the dissemination of false information and hate speech, and Article 45 on criminal sanctions significantly impact freedom of expression. The implementation of these provisions is often ambiguous and subjective, leading to potential misuse for suppressing criticism of the government and public officials. Although the 2024 amendments introduced changes, such as the removal of Article 27 paragraph (3) and the addition of Articles 27A and 27B, challenges persist due to vague legal language and severe penalties. This ambiguity creates a